Manajemen Penanaman Nilai Karakter dalam Pendidikan Kewarganegaraan pada Mahasiswa Bahasa Arab di IAIN Batusangkar - - Syaiful Marwan (Akademika: Jurnal Keagamaan dan Pendidikan, 2019)
This study aims to see the extent to which character values can be embedded in students in the management process in learning citizenship education. Limitation of value assessment is seen as limited to interactive social communication in the classroom through learning. Research method by describing how the process of managing learning itself. The results obtained are seen how the formation of student karate values in civic education through the interaction process in wellmanaged learning. With this result, even though there is only one semester of learning time, it can be seen that the character pattern that is embedded in students is done in Arabic language students.